Perancangan Motion Graphic Series sebagai Media Edukasi tentang Depresi bagi para Remaja - Joshua Rexy Lindartono; Saiful Yahya (LPPM STIKI Malang, 2022)
Depression is a familiar thing to everyone, depression is a mental disorder that can cause excessive sadness. All ages are susceptible to depression, especially adolescents aged 14-17 years, because they are experiencing changes biologically, psychologically, and socially. with the lack of concern for adolescents about depression is also one of the factors that make them susceptible to depression, besides that the lack of supporting media to provide education is a factor that make adolescents less concerned about this problem, social media such as Instagram and Youtube is one of the media that is often used by adolescents. The purpose of designing the Motion Graphic Series is to provide educational media for adolescents to become more understand, and also more concerned with, depression issues. This design uses the Design Thinking method which has several stages such as Understand, Observe, Point of View, Ideate, Prototype, and Test to get results that match the data that has been collected. This design produces a Motion Graphic Series as the main media to be asked on Youtube. and Instagram, besides that there are also supporting media in the form of advertisements on Youtube and Instagram to support the main media, the results of the trial work show that this Motion Graphic can help identify depression because it fits the target audience. From the results of this design, there is three series of Motion Graphic and also some media implementations such as Instagram posts and YouTube ads.